High-dose Carboplatin/Etoposide/Melphalan increases risk of thrombotic microangiopathy and organ injury after autologous stem cell transplantation in patients with neuroblastoma. (October 2018) - Jodele, Sonata; Dandoy, Christopher; Myers, Kasiani; Wallace, Gregory; Lane, Adam; Teusink-Cross, Ashley; Weiss, Brian; Davies, Stella
Abstract Transplant-associated thrombotic microangiopathy (TA-TMA) is an increasingly recognized complication of hematopoietic cell transplant that can result in multi-organ failure (MOF). Patients undergoing high-dose chemotherapy with autologous stem cell transplant (aHCT) for neuroblastoma require good organ function to receive post-transplant radiation and immunotherapy. We examined TA-TMA incidence and transplant outcomes in patients with neuroblastoma receiving different transplant preparative regimens. Sixty patients underwent aHCT using high-dose chemotherapy: 41 patients received carboplatin/etoposide/melphalan (CEM), 13 patients busulfan/melphalan (Bu/Mel) and six patients received tandem transplant (cyclophosphamide/thiotepa and CEM). TA-TMA with MOF was diagnosed in 13 patients (21.7%) at a median of 18 days after aHCT. TA-TMA occurred in 12 patients receiving CEM and in 1 after cyclophosphamide/thiotepa. There were no incidences of TA-TMA after Bu/Mel regimen. Six of 13 patients with TA-TMA and MOF received terminal complement blocker eculizumab for therapy. They all recovered organ function and received planned post-transplant therapy. Out of seven patients who did not get eculizumab, two died from TA-TMA complications and four progressed to ESRD. We conclude that the CEM regimen is associated with a high incidence of clinically significant TA-TMA after aHCT and eculizumab can be safe and effective treatment option to remediate TA-TMA associated MOF.